2001
DOI: 10.1253/jcj.65.381
|View full text |Cite
|
Sign up to set email alerts
|

Resting Ultrasonic Tissue Characterization and Dobutamine Stress Echocardiography for Prediction of Functional Recovery in Chronic Left Ventricular Ischemic Dysfunction.

Abstract: revious studies have shown the usefulness of lowdose dobutamine stress echocardiography (DSE) for the assessment of viable myocardium and the prediction of functional recovery after revascularization in patients with chronic coronary disease. [1][2][3][4][5][6][7][8] However, there were wide ranges of sensitivity, specificity, and accuracy (74-91%, 73-95%, and 73-91%, respectively) for prediction of reversible dysfunction, possibly because most studies included patients with various degrees of regional and glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…As mentioned before, the temporal relationship of CV with the cardiac cycle is also a useful marker of myocardial viability. 7 In the present study, the normalized time delay was, though used as a cutoff point for grouping, significantly longer in group B than in group A, which supports the data of Pasquet et al 8 and Homma et al 9 in patients with chronic ischemic LV dysfunction as well as those with an acute MI. 7 …”
Section: Role Of Ibs In the Assessment Of Myocardial Viabilitysupporting
confidence: 90%
See 3 more Smart Citations
“…As mentioned before, the temporal relationship of CV with the cardiac cycle is also a useful marker of myocardial viability. 7 In the present study, the normalized time delay was, though used as a cutoff point for grouping, significantly longer in group B than in group A, which supports the data of Pasquet et al 8 and Homma et al 9 in patients with chronic ischemic LV dysfunction as well as those with an acute MI. 7 …”
Section: Role Of Ibs In the Assessment Of Myocardial Viabilitysupporting
confidence: 90%
“…Takiuchi et al used it to assess myocardial viability in patients with reperfused acute MI and found that the recovery of visually assessed regional contraction followed that of CV (for both magnitude of CV and normalized time delay). 7 For patients with chronic LV ischemic dysfunction, on the other hand, Pasquet et al 8 and later Homma et al 9 showed the usefulness of IBS for assessing contractile reserve in combination with dobutamine echocardiography. Naito et al demonstrated that in patients with a remote MI, the magnitude of CV correlated with the percent 201 Tl uptake on perfusion imaging.…”
Section: Role Of Ibs In the Assessment Of Myocardial Viabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…24,25) Currently, sophisticated UCG techniques are used to improve the visualization of cardiac microstructure. [26][27][28] Ultrasonic tissue characterization such as integrated backscatter and tissue harmonic imaging may have enabled us to distinguish myocardial edema from hypertrophy in more detail.…”
Section: Discussionmentioning
confidence: 99%